Digital payment usage by MSME players in Bone regency: a theory of planned behavior and risk perception approach - Muh. Hasbi Ash. Shiddiq; Titiek Muthmainnah (IAEI, 2023)
This study aims to identify the factors influencing the intention to adopt digital payment methods among Micro, Small, and Medium Enterprises (MSMEs) in Bone Regency, South Sulawesi, using the Theory of Planned Behavior and perceived risk approach. Data were collected through online questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The findings of this study reveal that only two variables in the Theory of Planned Behavior significantly influence the intention to adopt digital payment methods among MSMEs, while perceived risk does not have a significant direct or mediating effect. The results indicate that MSMEs in Bone Regency are accustomed to using digital payments because they perceive it as a convenient method. Additionally, the ability to operate digital payments positively influences their intention to adopt. MSMEs in this study do not perceive any significant risks associated with digital payments.